Determination of lesion color for clustering psoriasis erythema - Hani, A.F.M. (CRC Press, 2014)
Psoriasis is an incurable but treatable skin disease and can exist for a long time 1. The disease is characterized by an abnormally high growth rate of new skin cells. Under normal conditions, skin cells will grow in approximately twenty-eight days, but in psoriasis the growth can occur in four days 2. Psoriasis is marked by the appearance of red lesions on body surfaces. At greater severities the lesion thickness increases, with coarse, slivery scales appearing. Psoriasis is not a contagious disease. Recent studies have shown that psoriasis can significantly affect quality of life, with many psoriasis patients experiencing social and psychological problems 3. The published psoriasis prevalence in Malaysia by the Dermatological Society of Malaysia is 3% 4. Of the 75,883 patients registered in the Hospital Kuala Lumpur from 2005 to 2010, 3,906 psoriasis patients were registered in the Dermatology Department, resulting in an incidence of 5.2% 5. Several examples of red plaques of psoriasis lesions and erythema severity levels are depicted in Figure 2.1. Â© 2014 by Taylor & Francis Group, LLC.